Integration of cubic motion and vehicle dynamic for yaw trajectory - Mat Ghani, Mohd. Firdaus (2014)
Researches in vehicle dynamic simulation have been a subject of interest for researchers nowadays. By replacing costly experiment, simulation of the vehicle dynamics can be the ultimate tools to investigate the vehicle response and produces similar results to that of real experiment. Many of the vehicle simulation inputs do not consider position of the car as a function of time. Cubic motion curve will be used as the input to the vehicle simulation and driver model system. Cubic motion is a curve generated by the integration of cubic spline and the dynamics of a vehicle. Cubic spline will generate the curve, while the dynamic of motion will position the vertices based on a given time set. hence, a new approach has been made to investigate the road input with time function to produce similar response compared to the experimental method. This research focuses on a two-degree-of-freedom vehicle lateral dynamic model. The tests were carried out for a two case studies which are double lane change and slalom test. Results have shown that, cubic motion can be used as the input for the vehicle simulation because it can produce good trajectory as well as other vehicle response such as vehicle trajectory, lateral acceleration and yaw rate. The significance of this research has a great potential for road safety study related to defining the speed limit of the vehicle according to the curviness of the road.